Gamifikasi Dalam Pembelajaran Bahasa Indonesia: Studi Efektivitas Game Interaktif Dalam Peningkatan Literasi Digital Siswa - Anita Candra Dewi (Jurnal Sultra Elementary School, 2025)
This study aims to explore the effectiveness of interactive games in improving digital literacy of students at the senior high school (SMA) level, especially in Makassar City. The method used in this study is quantitative with a quasi-experimental design, which is designed to compare two groups of students. The experimental group received gamification-based learning, while the control group followed conventional learning methods. A total of 120 students from SMA Negeri 17 Makassar and SMA Negeri 5 Makassar were involved in this study, which were then divided into two groups. For data collection, this study involved a digital literacy test consisting of a pre-test and post-test, along with observations and questionnaires that explored students' perceptions regarding their experiences. The results of the analysis showed a significant increase in digital literacy scores for the experimental group compared to the control group. The average score on the post-test of the experimental group was recorded at 82.5, while the control group only had an average score of 72.3. Through the t-test, a significant difference was found (p <0.05), indicating that the learning method with interactive games was proven to be more effective in improving students' digital literacy. In addition, the results of the questionnaire showed that 87% of students found it easier to understand the lesson material through interactive games, and 82% of students felt more motivated to learn.